Complex evaluation of the neurological status and metabolic effects of the vitamin-mineral complex Teravit Anti-Stress and its components - T. E. Bogacheva; A. G. Kalacheva; T. R. Grishina; O. A. Gromova (Фармакокинетика и Фармакодинамика, 2018)
In the experimental study, the effect of the vitamin-mineral complex Teravit Antistress and its individual components: Ginseng and Ginkgo Biloba on the orientation-research behavior, resistance to stress and the course of metabolic processes in laboratory rats were studied.